Direitos sexuais e reprodutivos: a situação das adolescentes privadas de liberdade em Sergipe - Rolemberg, Joira Alves de Lacerda Santos (2023)
In light of the critical-dialectical and feminist perspective, this dissertation seeks to focus on sexual and reproductive rights, as provided for in Law No. 12,594/2012, for adolescents complying with socio-educational internationalization measures. To this end, it understands the study as a central category of the capitalist system and how its reverberations and determinations directly influence the social relations that structure the Brazilian socio-historical formation. And also, how to interfere and reproduce inequalities, insertion, implementation and guarantee of equal rights for bodies with female gender identity. The research is exploratory, descriptive, with a qualitative approach, and based on bibliographical research, consultation of academic publications and access to institutional documents, seeking to develop reflections on issues of gender, sexuality, deprivation of freedom in female adolescence, based on our theorists who deepen studies on the topic at hand, creating a symbiosis between capitalism, patriarchy, feminism(s), sexual and reproductive rights. Having the SINASE law as a regulatory framework, the research followed publications from 2012 onwards, as well as considerations regarding the regulation of intimate visits at Fundação Renascer do Estado de Sergipe dated 2017. Finally, this study seeks to provoke reflection and promote proposals within its institutional scope to overcome the tensions that crystallize the exercise of sexuality in adolescence in deprivation of freedom, as well as suggesting possibilities for changes in the institutional reality